SAT0402 Safety of Etanercept Therapy in Hbsag Carriers with Ankylosing Spondylitis: A Prospective Study. (15th July 2016) - Fang, L.; Hu, Z.; Pan, Y.; Lin, Z.; Liao, Z.; Gu, J.
Abstract : Background: The prevalence rate of hepatitis B virus (HBV) infection in China (13%) and many other developing countries are much higher than that in developed countries. When anti-TNF agents are more available and affordable in developing countries, the safety of anti-TNF therapy in terms of the reactivation of hepatitis B virus (HBV) infection need more concern. Rare data from a prospective study focus on the use of TNF antagonists in patients with concurrent ankylosing spondylitis (AS) and HBV infection are available by now. Objectives: To evaluate the influence of Etanercept on the re-activation of HBV infection in HBsAg carriers with AS. Methods: In this 48 weeks observation, HBsAg carriers with active AS (BASDAI ≥4) despite failed treatment with at least two NSAIDs and sulfasalazine (for patients with persistent peripheral arthritis) were studied. Patients must have normal liver function prior to Etanercept therapy. All patients received the treatment of Etanercept 50mg each week. For patients who had positive HBV load (>100 copy/ml) at baseline, lamivudin were prescribed preventively. Pre-existing NSAIDs and sulfasalazine were allowed. During the study, serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and HBV load (polymerase chain reaction) were monitored every 6 weeks in the first 12 weeks and every 12 weeks after week 12. Increased AST/ALT and HBV load were managed and monitored according to expert opinion. After withdraw of Etanercept due to any reason, monitoring of ALT, AST and HBV load must be conducted until normal result was obtained in 2 consecutive tests. Results: Fourteen patients (12 male, 2 female) were recruited. At baseline, ten patients (group 1, including 1 female) had normal viral load (<100 copy/ml), other 4 patients (group 2, with preventive lamivudin) had abnormal viral load (4.7e4, 5.3e7, 2.8e3, 9.8e4 copy/ml, respectively). Two patients from group 1 and one patient from group 2 discontinued Adalimumab at week 12 due to ineffectiveness. Reactivation of hepatitis B occurred in one patient from group 1, and another from group 2. The patient from group 1 had mild elevated ALT and AST (71 and 46 IU/L, respectively) and increased HBV load (7.6e3) at Week 12. After prescription of Entecavir, abnormal laboratory finding was monitored every 4 weeks, both liver enzyme and viral load decreased to normal range in 8 weeks and remained normal. The patient from group 2 (baseline viral load 4.7e4) had mild elevated ALT and AST (57 and 49 IU/L, respectively) and increased HBV load (5.2e8) at week 24. After prescription of Adefovir (combined with the pre-existing Lamivudin), both liver enzyme and viral load decreased to normal range in 8 weeks and remained normal. For the rest 12 patients, no significant elevated AST/ALT or increased viral load was seen during follow-up. Conclusions: Etanercept therapy represent a safe and effective option for HBsAg carriers with AS refractory to traditional treatment. Prophylaxis strategy with more effective anti-viral drugs is recommended to reduce the risk of hepatitis B reactivation. Disclosure of Interest: None declared